Modeling and Electromagnetic Analysis of Multilayer Through Silicon Via Interconnect for 3D Integration - Zhaowen Yan; Ting Kang; Wei Zhang; Jianwei Wang (International Journal of Antennas and Propagation)
Convergence of multiple functions in a single device is the main thought behind the development of the current electronic trends. So, the requirement for higher integration in electronic devices has become more important in present days than in the past. Through silicon via (TSV) is the latest interconnect technology proposed mainly for higher integration and higher frequency. Therefore, cross talk will be an essential issue that needs to be taken into consideration. In this paper, we study the electrical property of a GSSG (S-Signal, G-Ground) TSV structure and propose the accurate lumped model which can be used to predict the TSV performance. Since more dies are used within one chip, the single layer TSV cannot satisfy the requirement. Hence, we propose the multilayer TSV structure and study how the bump radius, bump height, and underfill material affect the TSV transmission performance and coupling issue, so that we can conduct a good TSV design. Furthermore, three multilayer 4 × 4 TSV array models are proposed with different GS distribution to analyze the detailed coupling results.